2016
DOI: 10.1177/1558944716628499
|View full text |Cite
|
Sign up to set email alerts
|

Nonoperative Management of Acute Upper Limb Ischemia

Abstract: Background: Acute upper limb ischemia (AULI) is an uncommon emergency warranting immediate evaluation and treatment. The role of nonsurgical therapies including endovascular techniques, thrombolytics, and anticoagulation remains undefined. The authors systematically reviewed the current literature on the nonsurgical treatment of acute ischemia of the upper extremity. Methods: A PubMed and Embase search was conducted, and articles were screened using predetermined criteria. Data collected included patient demog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 48 publications
0
21
0
1
Order By: Relevance
“…Several recent studies demonstrated good results for percutaneous thrombus aspiration. 7,10 The latter proved efficient in our patient, aiding the prompt recanalization of his radial artery and the palmar arch. However, in the clear majority of the previously reported cases, percutaneous treatment was assessed using a transfemoral access, which may be technically challenging due to kinked iliac, subclavian, and axillary arteries; therefore, in such cases, a direct puncture of the brachial artery may be a useful alternative.…”
Section: Discussionmentioning
confidence: 66%
“…Several recent studies demonstrated good results for percutaneous thrombus aspiration. 7,10 The latter proved efficient in our patient, aiding the prompt recanalization of his radial artery and the palmar arch. However, in the clear majority of the previously reported cases, percutaneous treatment was assessed using a transfemoral access, which may be technically challenging due to kinked iliac, subclavian, and axillary arteries; therefore, in such cases, a direct puncture of the brachial artery may be a useful alternative.…”
Section: Discussionmentioning
confidence: 66%
“…17 However, there is a lack of good quality evidence for non-surgical treatment and poor functional outcomes were more often seen after conservative treatment. 18 Thrombolysis is also an option for treatment of upper limb vascular occlusions being locally effective, 19 but up to 33% of treated patients have complications with the risk of hemorrhage, cerebrovascular events, and even death with its usage. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is scant evidence for the safety and efficacy of massages. Treatment strategies for AULI, one of the possible massage complications, include thrombolytic therapy, endovascular intervention and surgical intervention [4], but many aspects of the treatment planning and decision making are determined by the practical capabilities and local availability of each facility [5].…”
Section: Introductionmentioning
confidence: 99%